DIFERENSIASI BERBAGAI MACAM EKSPLAN PADA PERBANYAKAN Philodendron goeldii (Araceae) SECARA IN-VITRO - Irawati Irawati (BERITA BIOLOGI, 2000)
Study on the differentiation of several explants by in vitro culture were conducted on Philodendron goeldii for propagationpurposes.Activated charcoal added to the initiating medium did not improve the development of the cultures.In general all type of explants were successfully differentiated into plantlets in all media tested. The most potential explants for propagation of this species are the shoot tip and the stem.Addition of 0.3 ppm NAA to the basal medium with different cytokinins induced roots development on shoot tips,petioles and young leaves cultures.The ability of culture to produce multiple shoots such as in medium with NAA + 2-iP or NAA + BA would give a better opportunity for in-vitro propagation of P. goeldii.